Cardiac cement embolism and asymptomatic pulmonary embolism caused by percutaneous vertebroplasty for osteoporotic vertebral fracture: a case report - Yang, Yang; Fei, Qi; Long, Gong Qian; Bo, Wu; Jun, Feng Ye; Rong, Zhang; Kui, Huang (Frontiers in Surgery, 2024)
BackgroundAs society ages, the incidence of osteoporotic vertebral compression fractures steadily rises. Procedures like percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP) have proven effective in significantly relieving pain in patients with these fractures. While PKP and PVP are minimally invasive, complications can still occur. However, most complications are not clinically significant, with cement leakage being the most common.Case presentationWe present the case of a patient with an osteoporotic vertebral compression fracture who underwent percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP). On the night following the procedure, the patient experienced transient discomfort in the chest, which resolved on its own. A chest CT scan the next day revealed a 5 cm arc-shaped high-density shadow near the right atrium, along with multiple high-density lung spots. After consulting with cardiothoracic surgery, interventional vascular surgery, and radiology experts, and discussing options with the patient and their family, a thoracotomy was recommended to remove the bone cement from the heart. However, the attempt was unsuccessful. Despite this, the patient made a good recovery and was successfully discharged.ConclusionsVascular leakage of bone cement is a potentially life-threatening complication of PKP/PVP, and it warrants careful attention.